CUSTOMER DELIGHT DAN ADVOKASI PASIEN: PERAN PELAYANAN PRIMA MENYENANGKAN PASIEN PADA KIDS DENTAL SPA - Tenovita Sari, Fajar; Purwanto, Purwanto; Fatchurrohman, Mochamad (ITB AAS Indonesia Surakarta, 2024)
Understanding how service excellence influences pediatric dental patient behavior is critical in formulating effective marketing strategies. This study examines the feelings and actions of patients (parents and children) when they receive excellent service compared to others, using the concept that emotions can be triggered by certain events to understand their impact on patient behavior (affective event theory). In a survey of 136 pediatric dental patients, we analyzed how service excellence affects three types of customer behavior: Customer delight, speaking positively about the product or service (customer advocacy), and patient loyalty. The results showed that excellent service increases (pediatric) patient delight, encouraging them to advocate and return for dental care. However, unexpectedly, our findings also show that the effect of service excellence in increasing patients' customer delight tends to be lower in those with a high tendency to seek attention (attention-seeking motive), due to a lack of authenticity or perceived benefit from the treatment received. Therefore, this study reveals the complex dynamics of service excellence in enhancing patient delight, advocacy, and patient loyalty, while demonstrating the importance of individual differences in influencing these processes.